2011
DOI: 10.1021/jp204193g
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeation and Separation in Functionalized Polymers of Intrinsic Microporosity: A Combination of Molecular Simulations and Ab Initio Calculations

Abstract: We combine molecular simulations and ab initio calculations to investigate the permeation and separation of CO2/N2 in polymers of intrinsic microporosity (PIMs) with different functional groups (cyano, trifluoromethyl, phenylsulfone, and carboxyl). A robust equilibration protocol is proposed to construct model membranes with predicted densities very close to experimental data. The fractional free volumes (FFVs) in PIM-1 (with cyano), TFMPS-PIM (with both trifluoromethyl and phenylsulfone), and CX-PIM (with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…We conclude that permeation through the (+ +)-PIM-CN membrane is based on as elective diffusion-permeation mechanism. [27,28] Them odified material (+ +)-PIM-CN had aspecific rotation of a ½ 25 589nm ¼ + 378.38 8 in THF and exhibited aCDspectrum very similar to that of (+ +)-PIM-CN. [26] 1 HNMR, 13 CNMR, and IR spectroscopy (see Figures S6-S8) showed that hydrolysis proceeded to over 90 %c onversion into carboxylic acid groups without appreciable loss of molecular weight (M n = 67 578 gmol À1 and M w = 123 760;some broadening of the PDI occurred, to 1.8).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…We conclude that permeation through the (+ +)-PIM-CN membrane is based on as elective diffusion-permeation mechanism. [27,28] Them odified material (+ +)-PIM-CN had aspecific rotation of a ½ 25 589nm ¼ + 378.38 8 in THF and exhibited aCDspectrum very similar to that of (+ +)-PIM-CN. [26] 1 HNMR, 13 CNMR, and IR spectroscopy (see Figures S6-S8) showed that hydrolysis proceeded to over 90 %c onversion into carboxylic acid groups without appreciable loss of molecular weight (M n = 67 578 gmol À1 and M w = 123 760;some broadening of the PDI occurred, to 1.8).…”
Section: Methodsmentioning
confidence: 96%
“…[33] (+ +)-PIM-CN can be chemically modified to expand the possible range of separation targets.T od emonstrate this possibility,weprepared acarboxylated derivative by subject-ing (+ +)-PIM-CN to acid hydrolysis to produce (+ +)-PIM-COOH (Scheme 1). [27,28] A decrease in the water contact angle of (+ +)-PIM-CN as compared to that of (+ +)-PIM-COOH from 1008 8 to 308 8 suggests that the (+ +)-PIM-COOH membrane is considerably more hydrophilic, aproperty that could be advantageous for the permeation of more-polar analytes (see Figure S9). According to the GPC results,the hydrolysis of (+ +)-PIM-CN with as trong acid was not destructive to the polymer backbone.…”
Section: Methodsmentioning
confidence: 99%
“…method was calculated to be 25.8 AE 0.5% which is slightly smaller than that of PIM-EA-TB (27.6%) 35 and of PIM-1 (28.8%). 36 The calculated fractional free volume conrms the poor polymer packing that is typical for all PIMs. The dihedral angle distribution for the MP structural unit observed within the packing simulation correlate well with the energy potential of deformation calculated by molecular dynamics (Fig.…”
Section: à3mentioning
confidence: 99%
“…The application of packing simulation to understand and predict the performance of PIMs as gas separation membranes (see below) is also an active area of research [100][101][102]. However, it should be noted that, at present, simulations of PIM packing do not take into account polymer dynamics, which are important for the accurate prediction of gas diffusivities, nor do they give information on possible swelling effects due to gas adsorption.…”
Section: Computer Simulationmentioning
confidence: 99%